Habituation of parasympathetic-mediated heart rate responses to recurring acoustic startle - Chen, Kuan-Hua; Aksan, Nazan; Anderson, Steven W.; Grafft, Amanda; Chapleau, Mark W. (Frontiers in Psychology, 2014)
Startle habituation is a type of implicit and automatic emotion regulation. Diminished startle habituation is linked to several psychiatric or neurological disorders. Most previous studies quantified startle habituation by assessing skin conductance response, eye-blink reflex, or motor response. The habituation of parasympathetic-mediated heart rate responses to recurrent startle stimuli is not well understood. A variety of methods and metrics have been used to quantify parasympathetic activity and its effects on the heart. We hypothesized that these different measures reflect unique psychological and physiological processes therefore may habituate differently during repeated startle stimuli. We measured cardiac inter-beat intervals (IBI) to recurring acoustic startle probes in 75 eight year old children. Eight acoustic stimuli of 500 ms duration were introduced at intervals of 15-25 seconds. Indices of parasympathetic effect included: 1) the initial rapid decrease in IBI post-startle mediated by parasympathetic inhibition; 2) the subsequent IBI recovery mediated by parasympathetic reactivation; 3) rapid, beat-to-beat heart rate variability measured from the first 7 IBIs following each startle probe. Skin conductance (reflecting sympathetic-mediated sweating) and motor responses to startles were also measured. Results showed that habituation of parasympathetic reactivation (IBI recovery and overshoot) and skin conductance responses were rapid and robust. In addition, changes in parasympathetic reactivation and skin conductance response were significantly correlated. In contrast, habituation of parasympathetic inhibition (the initial decrease in IBI) was slower and relatively modest. Measurement of rapid heart rate variability provided an index reflecting the combination of parasympathetic inhibition and reactivation. We conclude that different measures of parasympathetic activity habituate in a differential manner to repeated startle probes.